Therapeutic Aspects of Dogs with Presumptive Diagnosis of Idiopathic Epilepsy - Aiello, Graciane; Andrades, Amanda Oliveira de; Ripplinger, Angel; Polidoro, Dakir; Chaves, Rafael Oliveira; Ferreira, Priscila; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2017)
Background: Epilepsy is a chronic neurological condition characterised by recurrent epileptic seizures. Various antiepileptic drugs are used for the management of canine idiopathic epilepsy. Phenobarbital is the drug of choice for long-term treatment in dogs. Although it is well tolerated, phenobarbital can cause liver injury if administered alone or in combination with other drugs. Therefore, the main of this study was to identify dogs with presumptive diagnosis of idiopathic epilepsy and information about the antiepileptic drugs, the dose and frequency of administration, period of treatment, frequency of the seizure before and after start the treatment, complementary exams and adverse effects. Materials, Methods & Results: In this study were included 21 dogs with idiopathic epilepsy. All dogs were examined and having blood taken for blood count, biochemical tests (ALT, AST, AP, total protein, albumin, creatinine, urea, amylase, lipase, cholesterol and triglycerides), measurement of serum phenobarbital and/or potassium bromide and, some dogs, free T4 by dialysis and canine TSH. In this study, it was observed monotherapy (phenobarbital) in 76.19% (16/21), double therapy (phenobarbital and potassium bromide) in 19.05% (4/21) and triple therapy (phenobarbital, potassium bromide and gabapentin) in 4.76% (1/21) of dogs. The phenobarbital was used as monotherapy with dose between 1.4 and 12 mg kg-1 and the median of serum concentration was 26.41 μg kg-1. There was significant reduction in the frequency of the seizure after start the treatment. There was refractory to antiepileptic drugs in two dogs (9.5%). In blood analysis, there was increase serum activities of AP (23.81%) and ALT (14.20%), decrease total protein (42.29%), hypoalbuminemia (9.5%) and it was not increased AST activities. The main adverse effects were nodularliver damage and hypothyroidism. Discussion: In most cases of dogs with idiopathic epilepsy, monotherapy is preferred, because it tends to avoid complications that may arise from drug interactions and may also improve compliance by providing a simple treatment regimen. In this study, the phenobarbital controlled the seizures when used as monotherapy. It is considered success of an antiseizure drug when there is a reduction of seizure frequency by at least 50%, with minimal drug side effects. Approximately 20-30% of dogs with epilepsy do not have satisfactory seizure control or experience intolerable adverse effects with appropriate conventional medical treatment. In this study, there was refractory to antiepileptic drugs in 9.5%, one dog treated with phenobarbital and other with phenobarbital and potassium bromide. The long-term use of phenobarbital causes increase in liver enzymes, ALT and, mainly, ALP, these are attributed to enzymatic induction and to low degree of liver damage. ALT and AP increased the values and this does not necessarily indicate clinically significant liver damage or the need to stop therapy. The risk of liver toxicity appears to be greater with concentrations higher than 35 μg mL-1 or when multiple potentially hepatotoxic drugs are used. Other factors associated to the long-term use of anticonvulsant, such phenobarbital, potassium bromide or both, for the treatment of idiopathic epilepsy in dogs is acute pancreatitis and hypothyroidism. In this study, it was not observed acute pancreatitis, but there were two dogs with hypothyroidism. The long-term use of phenobarbital did not cause significant side effects, even with changes in the biochemical tests.